2005
DOI: 10.1074/jbc.m503969200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with PDZK1 Is Required for Expression of Organic Anion Transporting Protein 1A1 on the Hepatocyte Surface

Abstract: Although many organic anion transport protein (Oatp) family members have PDZ consensus binding sites at their C termini, the functional significance is unknown. In the present study, we utilized rat Oatp1a1 (NM_017111) as a prototypical member of this family to examine the mechanism governing its subcellular trafficking. A peptide corresponding to the C-terminal 16 amino acids of rat Oatp1a1 was used to affinity-isolate interacting proteins from rat liver cytosol. Protein mass fingerprinting identified PDZK1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 33 publications
5
105
0
Order By: Relevance
“…The CL tot of ELT in pdzk1(Ϫ/Ϫ) mice was not completely reduced but was significantly lower than that in wild-type mice (77.3 Ϯ 4.9 and 55.2 Ϯ 3.9 in wild-type and pdzk1(Ϫ/Ϫ) mice, respectively; n ϭ 4 for each). PDZK1 regulates expression and/or localization of various transporters in vivo (Wang et al, 2005;Sugiura et al, 2008). In particular, Oatp1a1 is down-regulated in pdzk1(Ϫ/Ϫ) mice (Wang et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CL tot of ELT in pdzk1(Ϫ/Ϫ) mice was not completely reduced but was significantly lower than that in wild-type mice (77.3 Ϯ 4.9 and 55.2 Ϯ 3.9 in wild-type and pdzk1(Ϫ/Ϫ) mice, respectively; n ϭ 4 for each). PDZK1 regulates expression and/or localization of various transporters in vivo (Wang et al, 2005;Sugiura et al, 2008). In particular, Oatp1a1 is down-regulated in pdzk1(Ϫ/Ϫ) mice (Wang et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid DNA encoding human OATP1B1, OATP1B3, OATP2B1, organic cation transporter (OCT) 1, or OCTN2, all of which had been subcloned in pcDNA3 vector, was transiently transfected into HEK293/PDZK1 cells according to the calcium phosphate precipitation method. This HEK293/ PDZK1 cell line was used because the PDZ adaptor protein PDZK1 increases the transport activity of various xenobiotic transporters in vitro (Sugiura et al, 2006) and regulates expression of basolateral membrane transporter in hepatocytes in vivo (Wang et al, 2005), although a possible interaction of PDZK1 with OATP1B1, OATP1B3, OATP2B1, or OCT1 has not yet been examined. At 48 h after transfection, the cells were harvested and suspended in transport buffer, and uptake studies were performed by the silicon oil layer method as described above using isolated hepatocytes.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23] Furthermore, PDZK1 was demonstrated to be a critical determinant for the proper subcellular localization and function of rat Oatp1a1. 24 The transcriptional regulation of basolaterally expressed MRPs is not fully elucidated. Studies in mice support the notion that Mrp3 and Mrp4 are induced through a pregnane X receptor-mediated pathway.…”
Section: Hepatic Transport Systemsmentioning
confidence: 99%
“…However, most of the data suggesting such functional regulation by PDZK1 were obtained in in vitro double-transfection studies with cultured cell lines. Although Wang et al (2005) recently showed an essential role of PDZK1 in basolateral expression of organic anion transporting peptide 1a1 in the liver, the in vivo evidence for a fundamental role of PDZK1 as a regulatory mechanism for xenobiotic transporters is quite limited in small intestine.…”
mentioning
confidence: 99%